Three-phase synchronous PWM for flyback converter with power-factor correction using FPGA ASIC design - Omar, A.M.; Rahim, N.A.; Mekhilef, Saad (Institute of Electrical and Electronics Engineers (IEEE), 2004)
The design and development of a synchronous pulsewidth modulation (PWM) generator suitable for the three-phase flyback converter with transformer isolated and power-factor correction using a field-programmable gate array is proposed. The proposed three-phase synchronous PWM makes it possible for the converter to obtain the sinusoidal supply currents with a near-unity power factor. A high-frequency transformer is considered in the design to provide galvanic isolation and serves the dual role of inductor and transformer. Results are provided to demonstrate the effectiveness of the design.